Effect of different artificial sweeteners on protein glycation - Kumar, Dinesh; Ali, Ahmad (Acta Biologica Szegediensis, 2023)
Glycation refers to the non-enzymatic molecular interaction between carbonyl group of sugars and amino groups of macromolecules viz. proteins, DNA, and lipids leading to the generation of Schiff’s base, Amadori products, and finally converted to deleterious advanced glycation end-products (AGEs). Several diseases such as neurodegenerative or mental disorders, cardiovascular complications, as well as diabetes, and its related complications show glycated product involvement. Hyperglycemia and diabetes are the main diseases in which AGEs formation and its accumulation are enhanced and cause secondary complications. This study was performed to investigate the antiglycation and anti-aggregation potential of Food and Drug Administration-approved artificial sweeteners. The in vitro glycation system (BSA and glucose) was incubated along with artificial sweeteners viz acesulfame potassium, saccharin sodium, sucralose, aspartame, and neotame for 35 days at 37 °C. The conventional analytical methods such as browning, NBT assay, DNPH assay, and assessment of fluorescent AGEs were carried out spectroscopically to check the amount of glycation products. The presence of the mentioned artificial sweeteners in the glycation system showed inhibition of carbonyl content, total AGEs generation, and aggregation of β-amyloid structures. On day 35, acesulfame potassium reduced carbonyl content by 62.63 ± 0.91%, total AGEs generation by 49.39 ± 0.82%, and β-amyloid aggregation observed by Thioflavin-T assay by 43.45 ± 1.14%. The tested artificial sweeteners exhibited potential antiglycation and anti-aggregation activity in vitro in protein, BSA. They may be used as a therapeutic agent for the management of diabetes and its complications.